Extracorporeal membrane oxygenation: beyond rescue therapy for acute respiratory distress syndrome?. Issue 1 (February 2017) - Combes, Alain; Bréchot, Nicolas; Luyt, Charles-Edouard; Schmidt, Matthieu
Abstract : Purpose of review: This article summarizes the results of past and more recent series on venovenous extracorporeal membrane oxygenation (VV-ECMO) and discusses its potential indications beyond the rescue of patients with lung failure refractory to conventional mechanical ventilation. Recent findings: Successful VV-ECMO treatment in patients with extremely severe influenza A(H1N1)-associated acute respiratory distress syndrome (ARDS) and positive results of the CESAR trial have led to an exponential use of the technology in recent years. Beyond its currently accepted indication as a salvage therapy in ARDS patients with refractory hypoxemia or unable to tolerate volume-limited strategies, VV-ECMO may improve the outcomes of less severe ARDS patients by facilitating lung-protective ventilation. Summary: As initiation of VV-ECMO allows significant decrease in tidal volume, plateau and driving pressures, which has been associated with improved survival in ARDS patients, new trials should evaluate the impact of its early initiation in patients with severe but not refractory ARDS.